Peran Mahasiswa PPKN FIS Universitas Negeri Medan Dalam Menghadapi Tantangan Politik 2024, Studi Kasus: Praktek Money Politik - Linton Naibaho; Johan Pardamean Simanjuntak; Yana Sebha Pasaribu; Roselli Anjelina Lumbansiantar; Nelly Moria Hutapea; Ivana Theo Philia; Kania Nova Ramadhani; Tri Santa Mahulae (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Money Politics is an attempt to bribe voters by providing money or services so that voters' vote preferences can be given to a briber. Political money is no longer surprising, it is a common thing that happens when it comes to elections, parties do various things to get votes from the people, this political money has been passed down from generation to generation. Violations that often occur during elections include the widespread practice of money politics. Money politics is considered a practice that injures democracy. Elections are a big party in democracy where every citizen is free to give their voting rights to the parties that are nominating. In the lead up to the election, many candidates are chosen by the party to take part in the community by giving gifts. This is what we often refer to as "Money politics", this cannot be avoided, because of this people become unstable in their choices. The aim of this research is to find out the political challenges in general elections, find out what factors cause the practice of money politics in general elections and to find out how to face these political challenges. The research method used by the author is a qualitative method, which is descriptive research and tends to use analysis. The aim is to explain a phenomenon in as much depth as possible by collecting data in as much depth as possible, with greater emphasis on the depth of the data obtained. Students have an important role in fighting money politics. As students who study politics, it is only natural that they can form public awareness by providing political education or education for the community or others around us about the importance of integration in politics, and encouraging transparency and accountability in general elections and so that they are more aware of the dangers of money politics so that with Education to the public will increase people's understanding of the dangers of money politics and they will be wiser in choosing a good and wise leader. And society will not be more easily influenced by using political money. By getting involved in anti-money politics campaigns and fighting for policies that reduce corruption and the influence of money in politics, students can help create a more just and democratic political system.